IMPROVEMENT OF THE MILLET MILLING MACHINE - Neri, Alfredo C.; Mondejar, Jeremy P. (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 18 No. 2, 2015, 2018)
Please see PDF file.